1997
DOI: 10.1183/09031936.97.10112539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thoracic irradiation on hepatocyte growth factor in rats lung and in bronchoalveolar lavage fluid of patients with thoracic malignancies

Abstract: This study aimed to examine the physiological role of hepatocyte growth factor (HGF) after thoracic irradiation.We analysed the changes of HGF protein levels in rat lung following 12 Gy of whole thoracic irradiation. Bronchoalveolar lavage fluid (BALF) was then collected from 11 patients (10 lung cancer and one oesophageal cancer) after completion of radiation therapy.One month after irradiation, the HGF protein level in the lungs of irradiated rats decreased (p<0.05), followed by a remarkable elevation in HGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…HGF remained below detected levels throughout the examined period of examination in the plasma. Yamazaki et al [ 233 ] TGF-β Wistar Hsd/cpb Right lung X-ray/18 Gy 1, 4, 7, 10 d and 2–34 w PAI-1 bioassay Plasma No significant changes in levels of TGF-β were observed at Days 1, 4, 7, 1 0 or 14 after irradiation. The first increase was observed at 16 w, with a maximum at 20 w. Vujaskovic et al [ 234 ] IL-4 Fischer-344 Right lung X-ray/20 Gy 1, 7, 14, 21, 28, 56 and 84 d RNA assay + WB Lung tissue IL-4 mRNA was upregulated in the irradiated lung tissue.…”
Section: Cytokine Responses To Radiationmentioning
confidence: 99%
“…HGF remained below detected levels throughout the examined period of examination in the plasma. Yamazaki et al [ 233 ] TGF-β Wistar Hsd/cpb Right lung X-ray/18 Gy 1, 4, 7, 10 d and 2–34 w PAI-1 bioassay Plasma No significant changes in levels of TGF-β were observed at Days 1, 4, 7, 1 0 or 14 after irradiation. The first increase was observed at 16 w, with a maximum at 20 w. Vujaskovic et al [ 234 ] IL-4 Fischer-344 Right lung X-ray/20 Gy 1, 7, 14, 21, 28, 56 and 84 d RNA assay + WB Lung tissue IL-4 mRNA was upregulated in the irradiated lung tissue.…”
Section: Cytokine Responses To Radiationmentioning
confidence: 99%
“…HGF production is transiently suppressed in the irradiated area after irradiation. 18 In this study, it was also revealed that the biomarkers in blood were outperformed by those in BALF with regard to the screening efficiency for small pulmonary nodules. Although the sensitivity of VEGF, TGF-β and HGF in blood for screening small pulmonary nodules was rather considerable, its specificity appeared deficient in comparison.…”
Section: Discussionmentioning
confidence: 61%
“…The upregulation of these biomarkers signifies the development and/or metastasis of primary lung cancer. [9][10][11][12][13][14][15][16][17][18][19] Meanwhile, for the reason that histopathological specimen of small pulmonary nodules less than 8 mm is intractable to be obtained and biomarkers in peripheral blood of patients generally elevate at late stage of lung cancer, biomarkers in BALF seems to be a more appropriate manner to be adopted in preliminary screening procedure of small pulmonary nodules which usually suggest potential malignancy at early stage. 3,4,[20][21][22][23] Thus, we postulated that the level of IL-6, TNF-α, VEGF, TGFβ, HGF, as well as CEA in BALF may have some value in the screening process of patients with cancer-suspicious pulmonary nodules less than 8 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The HGF/MET axis is believed to contribute significantly to proliferation, metastasis, extracellular matrix remodeling, tumor cell survival, and angiogenesis associated with tumors [176,177,178]. MET , originally identified as a proto-oncogene [179,180], was found to be up-regulated in a variety of cancers, inducing its constitutive expression [181,182,183,184,185,186].…”
Section: Biological Functions Of Hgf and Its Isoformsmentioning
confidence: 99%